Stimulus Orang Tua dan Status Gizi dalam Hubungannya dengan Pertumbuhan dan Perkembangan Anak di Masa Pandemi Covid-19 - Yuni Candra Eka Putri Purnaning; Sulastyawati Sulastyawati; Sumirah Budi Pertami; Nurul Pujiastuti (FORIKES, 2023)
Parental stimulation and children's nutritional status is one of the factors that influence children's development. However, the fact is that not all parents have enough time and are able to provide stimulus and good nutrition for their children. This study aims to explain the relationship between parental stimulation and nutritional status with the development of children aged 3-5 years during the Covid-19 pandemic. This study applied a cross-sectional design, involving 22 respondents who were selected randomly. The instruments used were a stimulus questionnaire for age-appropriate child development and a developmental pre-screening questionnaire (KPSP) according to the child's age. Data were analyzed descriptively, followed by a correlation test. The results of the analysis showed that the p-value of the correlation test was 0.034 for the correlation between parental stimulus and child development and 0.000 for the correlation between nutritional status and child development. It was concluded that there was a relationship between parental stimulation and nutritional status with the development of children aged 3-5 years during the Covid-19 pandemic.Keywords: parental stimulus; nutritional status; child development ABSTRAK Stimulus orang tua dan status gizi anak merupakan salah satu faktor yang mempengaruhi perkembangan anak. Namun faktanya tidak semua orang tua memiliki waktu yang cukup dan mampu memberikan stimulus serta gizi yang baik bagi anak. Penelitian ini bertujuan untuk menjelaskan hubungan antara stimulus orang tua dan status gizi dengan perkembangan anak usia 3-5 tahun di masa pandemi Covid-19. Penelitian ini menerapkan rancangan cross-sectional, yang melibatkan 22 responden yang dipilih secara random. Instrumen yang digunakan adalah kuesioner stimulus untuk perkembangan anak sesuai usia dan Kuesioner Pra Skrining Perkembangan (KPSP) sesuai usia anak. Data dianalisis secara deskriptif, dilanjutkan dengan uji korelasi. Hasil analisis menunjukkan bahwa nilai p dari uji korelasi adalah 0,034 untuk korelasi antara stimulus orang tua dengan perkembangan anak dan 0,000 untuk korelasi antara status gizi dengan perkembangan anak. Disimpulkan bahwa ada hubungan antara stimulus orang tua dan status gizi dengan perkembangan anak usia 3-5 tahun di masa pandemi Covid-19.Kata kunci: stimulus orang tua; status gizi; perkembangan anak